Production of Beta-Carotene by Dunaliella Salina : Effect of Nano3 Concentration and Light Intensity - Nur Isma Idayu, Ismail (2012)
Beta-carotene is used as vitamin A precursor and its antioxidant property has been used in dietary supplements for the prevention of diseases such as cancer and coronary heart disease. The purpose of this study is to study the effect of NaNO3 concentration and light intensity to the growth and production of beta-carotene by Dunaliella salina. Four different NaNO3 concentrations (100%, 75%, 50%, and 25% v/w) and light intensities (6000 lx, 8000 lx, 11000 lx and 17000 lx) were used. Cell growth was determined by cell counting method and analysis of total beta-carotene concentration in the samples was done using High Performance Liquid Chromatography (HPLC). From the result obtained, the NaNO3 concentration and light intensity will affect the growth of Dunaliella salina, where the growth was reduced due to NaNO3 starvation and it was also induced with the high light intensity until nitrate became the limiting source for the cells. Besides that, NaNO3 concentration and light intensity will also affect the beta-carotene production of Dunaliella salina, where the production was increased as the NaNO3 concentration was decreased and the light intensity was increased until the concentration of NaNO3 has become the limiting factor of the experiment. In order to improve the research, further study to identify the optimal NaNO3 concentration and light intensity required for maximizing the production of beta-carotene by Dunaliella salina shall be done.